Non-allergic activation of eosinophils after strenuous endurance exercise - McKune, AJ; Smith, LL; Semple, SJ; Wadee, AA (South African Journal of Sports Medicine, 2004)
Objective. To determine the effect of prolonged endurance exercise on the serum concentrations of eosinophil cationic protein (ECP), immunoglobulin E (IgE) and upper respiratory tract symptoms (URTS). Design. In 11 healthy, experienced volunteers (6 males, 5 females, age 43 ± 9.8 years) the serum concentrations of ECP and IgE were measured, 24 hours prior to projected finishing time, immediately post exercise (IPE), and 3 h, 24 h, and 72 h after an ultramarathon (90 km). Self-reported URTS were also recorded for 14 days after the race. ECP was measured using radioimmunoassay and IgE using the Alastat Microplate Total IgE kit. The after-exercise values were corrected for plasma volume changes, which were calculated from haematocrit and haemoglobin values. Serum concentrations of ECP and IgE were analysed using an analysis of variance (ANOVA) comparing values with before-exercise levels. Level of significance was set at p ≤ 0.05. Results. ECP was significantly elevated at 72 hours (+52%), whilst IgE was not significantly altered after the ultramarathon. There were no reported URTS for the 14 days after the race. Conclusion. The eosinophil is a pro-inflammatory leukocyte involved in bronchial hyperreactivity and allergic inflammation of the airways. IgE is associated with allergic diseases such as asthma and rhinitis. Serum ECP is a sensitive marker of eosinophil activation. The result provides evidence for the non-allergic activation of blood eosinophils during prolonged endurance exercise. Whether this indicates exercise or environmentally induced airway inflammation, or a role for ECP in muscle /tissue repair, are hypotheses that require additional research. SA Sports Medicine Vol.16(2) 2004: 12-16